Opportunities and Challenges for the Use of Alternative Vehicles in Sofia - Results of the Survey - Petrov, Emil (Research Papers, 2021)
This report is a continuation of the author’s research on alternative ways for transportation. An own survey was conducted, aimed at the users of personal and rented electric scooters in Sofia and in particular – in its central part of the city. It aims to identify the problems identified by consumers, their nature, origin, and the consumers are asked to give recommendations for their solution. Tourists also play an important role, as scooters are extremely convenient to reach and move between tourist sites, which are usually located in this part of the city. The derived recommendations can be used both by Sofia Municipality in the formation of its policy regarding micromobility or for the implementation of specific measures, as well as by the companies providing the service „electric scooter rental“ to improve its quality, incl. and for their more successful use by tourists, visiting the destination Sofia.